A Governmental Approach to Address Risks from Cryptocurrencies: Focusing on South Korea - Jung, Jeyong; Chun, Yong-tae (International Journal of Engineering and Technology, 2018)
Background/Objectives: Cryptocurrency-related risks range from fraud, to hackings, and to money-laundering, terrorist financing, and tax-evasion. This study aims to investigate how the Korean government has developed and implemented regulatory policies.Methods/Statistical analysis: This study draws on documentary research. Various documents were used, mainly including government publications, research papers, and trend analysis reports. Documentary research was an appropriate method in this research. Firstly, there has not been enough attention to this research topic, which needed to acquire contextualized knowledge before carrying out empirical research. Secondly, performing empirical research was not feasible at the time of this research due to fast-changing technical elements.Findings: To effectively control misuse of cryptocurrencies, the Korean government has developed and enforced regulatory policies. The government policies were manifestations of an interdepartmental approach initiated by the higher government. However, those regulatory policies were not based upon any comprehensive regulatory framework tailored to cryptocurrencies. Also, two strands of regulatory strategies were adopted. The first strategy focused on regulating cryptocurrency exchanges. Those exchanges were found to be the least regulated by the government unlike comparable financial exchanges. This approach could be effective in that individual users were required to use traditional banking services when buying and selling cryptocurrencies. The second strategy depended on the pre-existing financial regulatory framework by utilizing public financial institutions. This traditional regulatory framework included watchdog agencies, banks, and credit card companies. The financial regulatory framework also set the boundary for relevant policies of non-financial institutions. In this respect, non-financial institutions involved did not have a clear presence in the framework, while public financial institutionsâ€™ role was extensive enough to put pressure on cryptocurrency exchanges.Improvements/Applications: The governmental approach to cryptocurrencies needs to be revamped over time because the contextual factors change constantly. It needs to incorporate governmentâ€™s responses as well as market trends.Â Â